The Effect of Work-Life Balance, Work Environment, and Career Development on Employee Retention through Work Motivation as an Intervening Variable: A Case Study of Generation Z in a Property Company in Tangerang Regency - Nindy Lourentsya; Nana Sutisna (LPPM Universitas Buddhi Dharma, 2026)
This study examines the influence of work-life balance, work environment, and career development on employee retention, with work motivation serving as an intervening variable. The primary issue explored is how property companies can retain employees by analyzing their perceptions of work-life balance, work environment, and career development through work motivation, particularly among Generation Z. The purpose of this thesis is to determine the extent to which these selected variables affect employee retention in property companies in Tangerang, as many Gen Z employees today tend not to stay long when entering the workforce for the first time. This case study employs a qualitative approach using the Structural Equation Modeling (SEM) method on 115 active Gen Z respondents who met the criteria. The results show that work-life balance does not significantly influence employee retention, nor does the work environment. Only career development has a significant effect on retention, as many employees are highly concerned about career growth, which motivates them to remain with the company. These findings provide new insights indicating that, within the real estate/property sector, employee retention is not dependent on work–life balance, as flexible working hours and the work environment tend to be overlooked by Gen Z employees. Instead, Generation Z prioritizes career and positional advancement as the primary factor influencing their decision to stay or leave.